Avaliação de aprendizagem e de recombinação de leitura por meio de um procedimento de pareamento entre estímulos - Mengatto, Giulia (Universidade Federal de São Carlos, 2025)
The objective of the present study was to evaluate the effect of a stimulus-stimulus (S-S) matching procedure (written words and pictures) on (a) the emergence of reading the words presented during the matching tasks and (b) the emergence of reading new words formed by recombining syllables from the matched words (as a measure of generalization through unit recombination). A total of 16 participants (ages 6–8; 8 participants in Experiment 1 and 8 in Experiment 2) were exposed to the experimental procedures. In both experiments, the main task was S-S matching between written words and pictures. A total of 21 experimental words were used: 9 teaching words, 6 control words, and 6 generalization words (formed by recombining syllables from the teaching words). The S-S (word-picture) matching procedure was conducted only with the teaching words. The control words were presented only during assessment tasks and did not include syllables used in the teaching words. In the first experiment, four participants completed the planned procedures, three of whom learned to read the teaching words after exposure to the S-S matching procedure but did not maintain reading accuracy over time. Data collection for the remaining participants was interrupted due to the end of the school term. In the second experiment, five children completed the planned activities. Of those, three showed evidence of learning to read the teaching words used in the S-S matching procedure, while two participants did not show evidence of reading acquisition for the teaching words. The other participants did not complete the instructional procedures due to the end of the school term. In both experiments, none of the participants showed accurate reading responses for the control or generalization words.
Evaluation of learning and reading recombination using a stimulus matching procedure
Keywords: Leitura; Pareamento de estímulos; Generalização recombinativa; Recombinative generalization; Matching to sample; Reading; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::APRENDIZAGEM E DESEMPENHO ACADEMICOS